2015
DOI: 10.1002/2015ja021634
|View full text |Cite
|
Sign up to set email alerts
|

Plasma turbulence and coherent structures in the polar cap observed by the ICI‐2 sounding rocket

Abstract: The electron density data from the ICI‐2 sounding rocket experiment in the high‐latitude F region ionosphere are analyzed using the higher‐order spectra and higher‐order statistics. Two regions of enhanced fluctuations are chosen for detailed analysis: the trailing edge of a polar cap patch and an electron density enhancement associated with particle precipitation. While these two regions exhibit similar power spectra, our analysis reveals that their internal structures are significantly different. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 81 publications
(202 reference statements)
7
29
1
Order By: Relevance
“…Kelley et al [] suggested that much of large‐scale structures in the high‐latitude F region are caused by soft particle precipitation. The situation in the dayside cusp region was verified by the ICI‐2 rocket studies [ Moen et al, ; Spicher et al, , ]. However, it may not be the case in the nigthside auroral oval during a substorm.…”
Section: Discussionmentioning
confidence: 89%
“…Kelley et al [] suggested that much of large‐scale structures in the high‐latitude F region are caused by soft particle precipitation. The situation in the dayside cusp region was verified by the ICI‐2 rocket studies [ Moen et al, ; Spicher et al, , ]. However, it may not be the case in the nigthside auroral oval during a substorm.…”
Section: Discussionmentioning
confidence: 89%
“…According to Kintner and Seyler (), the range of scales where turbulence plays a relevant role is from few meters up to ∼1000 km in the topside F region of the high‐latitude ionosphere, a range of spatial scales where large magnetic and electric field fluctuations have been observed. In recent years, an extensive literature has demonstrated that high‐latitude magnetic and electric field fluctuations, as well as plasma density variations, show scale‐invariance and intermittent turbulent features (De Michelis et al, ; ; Golovchanskaya et al, , Spicher et al, ; Tam Sunny et al, ). Furthermore, the scale‐invariance nature of magnetic field fluctuations has been shown to be a function of the different polar regions (polar cap, cusp, auroral oval), the magnetic local time, the interplanetary magnetic field conditions and the geomagnetic activity disturbance level (De Michelis et al, , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Various different approaches had been explored to understand nonlinear characteristics and intermittency in ionospheric irregularities, like structure function analysis (Dyrud et al, 2008;Spicher et al, 2015), fractal and multifractal analysis (Wernik et al, 2003;Alimov et al, 2008;Bolzan et al, 2013;Tanna and Pathak, 2014;Miriyala et al, 2015;Chandrasekhar et al, 2016;Fornari et al, 2016;Sivavaraprasad et al, 2018;Neelakshi et al, 2019), and multispectral optical imaging (Chian et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Structure function analysis performed on ionospheric high-latitude in situ data have revealed the intermittent nature of ionospheric irregularities owing to the large deviations from the Kolmogorov's K41 universal power-law index proposed for neutral fluid turbulence (Spicher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%